1997
DOI: 10.1182/blood.v89.6.1954
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Cleavage of Recombinant Type 2A von Willebrand Factor Mutants R834W and R834Q: Inhibition by Doxycycline and by Monoclonal Antibody VP-1

Abstract: The susceptibility of recombinant type 2A von Willebrand factor (vWF ) to a recently identified plasma metalloproteinase and the potential application of proteolysis inhibition in the treatment of the disease were investigated. Two recombinant type 2A vWF mutants, R834W and R834Q, were spontaneously cleaved by the partially purified plasma proteinase to smaller forms. When treated with guanidine HCl, both the wild-type and the R834W mutant vWF exhibited a biphasic change in proteolytic susceptibility, reaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 22 publications
3
37
0
Order By: Relevance
“…Investigation of the proteolysis of recombinant type 2A VWF mutants Arg1597Trp and Arg1597Gln revealed that both showed increased proteolysis compared with wild-type VWF and both are overtly susceptible to proteolysis: they exist in susceptible conformations and are cleaved under conditions that cause little cleavage of wild-type VWF (Tsai et al, 1997). Similar findings have been reported for various other type 2A VWD mutations (Lyons et al, 1994).…”
Section: Determinants Of Vwf Proteolysis By Adamts13supporting
confidence: 68%
See 1 more Smart Citation
“…Investigation of the proteolysis of recombinant type 2A VWF mutants Arg1597Trp and Arg1597Gln revealed that both showed increased proteolysis compared with wild-type VWF and both are overtly susceptible to proteolysis: they exist in susceptible conformations and are cleaved under conditions that cause little cleavage of wild-type VWF (Tsai et al, 1997). Similar findings have been reported for various other type 2A VWD mutations (Lyons et al, 1994).…”
Section: Determinants Of Vwf Proteolysis By Adamts13supporting
confidence: 68%
“…This appears paradoxical when compared with the abnormal multimer profile of type 2A VWD plasma VWF, which is also more susceptible to proteolysis by ADAMTS13. This paradox may be resolved by consideration of three points (Bowen, 2004): (i) The degree of susceptibility to proteolysis for Tyr/Cys1584 VWF is many fold smaller than that measured for a type 2A VWF; (ii) the proteolysis of Tyr/ Cys1584 VWF in vitro is dependent on mildly denaturing conditions [suggesting the need for fluid shear stress in vivo (Furlan et al, 1996)] whereas type 2A VWF may exist in a conformation which permits proteolysis in the absence of shear (Tsai et al, 1997); (iii) multimer analysis may be too insensitive to show subtle changes in the HMW fraction of plasma VWF.…”
Section: Determinants Of Vwf Proteolysis By Adamts13mentioning
confidence: 99%
“…Doxycycline, an inexpensive and relatively commonly prescribed tetracycline antibiotic, has been shown to inhibit proteolytic cleavage of vWF due to its metallic cation-binding activity. 73 Given this inhibition of metalloproteinase by doxycycline, it is plausible that doxycyclineinduced inhibition of ADAMTS-13 may confer protection against vWF degradation in the presence of LVAD-associated shear stress. This hypothesis was tested 74 with a variety of in vitro and ex vivo modeling.…”
Section: Target: Acquired Von Willebrand Diseasementioning
confidence: 99%
“…On cleavage, one N-terminal and one C-terminal fragment are generated from the VWF monomer (2)(3)(4)(5). Pathological perturbations of the ADAMTS13/VWF proteolytic interaction are responsible for either thrombotic microangiopathies or hemorrhagic syndromes in type 2A von Willebrand diseases (6)(7)(8)(9)(10)(11). Modulation of the ADAMTS13/ VWF interaction is critical for an efficient proteolysis and involves both VWF and ADAMTS13.…”
Section: Introductionmentioning
confidence: 99%